An exploration of clinical practice in sites with and without clinical nurse or midwife specialists or advanced nurse practitioners, in Ireland - ELLIOTT, NAOMI; COYNE, IMELDA; LALOR, JOAN; COMISKEY, CATHERINE; HIGGINS, AGNES (My University, 2016)
Background Clinical specialist (CS) and advanced practitioner (AP) roles have increased in nursing and midwifery internationally. This study explored clinical practice in sites with and without clinical nurse or midwife specialists or advanced nurse practitioners in Ireland. Methods Using a case study design, interview, observational and documentary data from postholding sites (CSs or APs employed) were compared with data from non-postholding sites (no CSs or APs employed). Interviews and observations were conducted with postholders (n = 23), and compared with data from healthcare professionals (nurses or midwives, doctors) (n = 23) in matched services. Interviews were held with Directors of Nursing and Midwifery (n = 23), healthcare professionals (n = 41), service users (n = 41) with experience of receiving care or working with postholders, and non-postholders in matched services. The data were analysed using Nvivo (Version 8). Results The findings suggest that postholders’ practice appeared to differ from non-postholders’ in relation to case management and service provision. Postholders were seen as having an impact on readmission rates, waiting lists/times, collaborative decision-making, continuity of care and workload management. Postholders’ autonomy to manage caseloads was perceived to lead to smoother transition of patients/clients through the healthcare system. Service-users’ self-reports appeared to appreciate the individualised holistic care provided by postholders. Postholders’ role in facilitating person-centred care and promoting interprofessional team working, are essential elements in quality care provision and in global healthcare workforce planning. Conclusions To meet changing healthcare demands, promote person-centred care, and improve service delivery, more specialist and advanced practice posts in nursing and midwifery should be developed and supported within healthcare.
PUBLISHED
April 26th
Keywords: Clinical specialist Advanced practitioner Nurses Midwives Case study Clinical practice; Clinical specialist Advanced practitioner Nurses Midwives Case study Clinical practice